Function of Motives in Karawo Gorontalo Embroidery Fabric - Wira Pratama Rumambie; Yusuf Affendi Djalari (Universitas Komputer Indonesia, 2021)
The purpose of this research is to see and categorize some of the functions of the Karawo embroidered cloth seeing from the motifs in Goronalo, Karawo itself is a typical traditional cloth originating from Gorontalo whose manufacture is produced by handicrafts. Karawo itself has a unique way of doing it, such as making karawo which requires patience and thoroughness, making karawo takes one week to make one karawo that is ready to use. To support the research, we use descriptive methods and the data collected in the preparation of journals are analyzed descriptively, data collection is also in the form of interview data and study results from literature sources. The results show that Gorontalo karawo embroidery has its own meaning to the function of the motifs that will be used as a complementary ornament of the cloth so that the karawo embroidery is formed. This is because each of the motifs continues to develop and shift to a more modern direction which makes the karawo motif in a certain function has its own meaning for its users which is then adjusted to what the consumer likes. However, this can add to the function of the more modern karawo motifs as time goes by which then choose to leave Gorontalo customary and cultural motifs. The conclusion of the research is to find that the karawo embroidery handicraft has a function of every motif that has been made, from traditional cultural motifs to modern motifs that tend to be liked or interested by users. Keyword: Culture; Embriodery; Gorontalo; Karawo; John and Fritz Koraag